Enclosing the right to fish: A Q-study into fishers' attitudes to rights in Scottish fisheries. (1st April 2020) - Weir, Stephanie; Kerr, Sandy
Abstract: Current management of Scottish fisheries uses a quota system that has marketized the right to fish and led to unforeseen social consequences including inequity and barriers to entry. The potential for reform has been brought to the public's attention following the United Kingdom's decision to leave the European Union. This paper maps the opinions of lead actors in the Scottish fishing industry to changing rights in fisheries and the future of the quota system at this tipping point. The analysis, done by Q-methodology, reveals three unique attitudes. These have been titled: the Investors; the Reformers; and the Realists. These divergent views expose points of tension within the fishing industry and demonstrate the need for including multiple understandings of ownership in future management schemes. The article concludes with a call for greater engagement with all voices in the industry to expose both divergent perceptions and industry consensuses for future policy. Highlights: Q-methodology used to reveal attitudes to issues of rights and ownership in Scottish fisheries. Three unique views emerged within the Scottish fishing industry. Divergent views indicate tensions between industry groups and multiplicity in understandings of fairness and ownership. Future management should take pluralities of understandings into account to prevent further inequity.